Genetic Testing for Malformations of Cortical Development: A Clinical Diagnostic Study - Straka, Barbora; Hermanovska, Barbora; Krskova, Lenka; Zamecnik, Josef; Vlckova, Marketa; Balascakova, Miroslava; Tesner, Pavel; Jezdik, Petr; Tichy, Michal; Kyncl, Martin; Musilova, Alena; Lassuthova, Petra; et al. (Neurology. Genetics, 2022)
BACKGROUND AND OBJECTIVES: Malformations of cortical development (MCD), though individually rare, constitute a significant burden of disease. The diagnostic yield of next-generation sequencing (NGS) in these patients varies across studies and methods, and novel genes and variants continue to emerge. METHODS: Patients (n = 123) with a definite radiologic or histopathologic diagnosis of MCD, with or without epilepsy were included in this study. They underwent NGS-based targeted gene panel (TGP) testing, whole-exome sequencing (WES), or WES-based virtual panel testing. Selected patients who underwent epilepsy surgery (n = 69) also had somatic gene testing of brain tissue-derived DNA. We analyzed predictors of positive germline genetic finding and diagnostic yield of respective methods. RESULTS: Pathogenic or likely pathogenic germline genetic variants were detected in 21% of patients (26/123). In the surgical subgroup (69/123), we performed somatic sequencing in 40% of cases (28/69) and detected causal variants in 18% (5/28). Diagnostic yield did not differ between TGP, WES-based virtual gene panel, and open WES (p = 0.69). Diagnosis of focal cortical dysplasia type 2A, epilepsy, and intellectual disability were associated with positive results of germline testing. We report previously unpublished variants in 16/26 patients and 4 cases of MCD with likely pathogenic variants in non-MCD genes. DISCUSSION: In this study, we are reporting genetic findings of a large cohort of MCD patients with epilepsy or potentially epileptogenic MCD. We determine predictors of successful ascertainment of a genetic diagnosis in real-life setting and report novel, likely pathogenic variants in MCD and non-MCD genes alike.